Women and mining: Resilience and marginalization in mining territories - Escalona Thomas, Daniela (Revista de Geografía Norte Grande, 2021)
The territorial irruption of mining is legitimized through discourses about development, economic growth and employment, however, in recent decades it has been shown that the results in local development are not what was expected. For women not only see their quality of life deteriorated and that of their families as a result of the mining spatial metabolism that produces territories at the service of this industry with a markedly masculine identity, but also they face difficulties to be part of this territory. Through interviews with key informants in the mining territory produced by Minera Los Pelambres in Choapa Alto, the limitations faced by women are identified and described, as well as the consequences in the work, social and domestic space suffered when they achieve with difficulty be part of the mining company or join the jobs derived from mining rent. The industry’s efforts to incorporate women and positively impact the territory are recognized, however, the results do not meet the expectations of its inhabitants since its transformation has reinforced traditional gender roles and identities, producing new challenges and limitations for them.